(untitled) (AYUSHDHARA, 2019)
Kasa roga is very common due to unfavorable environmental condition, Hence the disease ‘Kasa’ was selected for present study. In this research we have studied the Nidanpanchak of Vataj kasa, Pittaj kasa, and Kaphaj kasa and changes in values of total leucocyte count and differential leucocyte count. Those patients who were complaining the symptoms like Hrid pradeshi shool, Swarbheda, Shirshool, Shushk kasa considered as Vataj kasa. Urovidah, Trushna, Jwar, Chhardi were considered as Pittaj kasa and in Kaphaj kasa symptoms were Shiroruja, Kasa, Kaphashtivan and Kandu. Present study is to find the changes in total leucocyte count and differential leucocyte count in Vataj kasa, Pittaj kasa and Kaphaj kasa. The patients were more in number with Vataj kasa as compared to Pittaj and Kaphaj kasa. Total leucocyte count was seen more in Kaphaj kasa than in Pittaj and Vataj kasa. Neutrophil for Pittaj kasa was observed to be significantly higher than that of Kaphaj kasa but there was no significant difference between neutrophil of Pittaj and Vataj kasa as well as Kaphaj and Vataj kasa. Eosinophil was significantly observed in Kaphaj kasa as compared to Pittaj and Vataj kasa. Also, there was significant increase in Vataj kasa than Pittaj kasa. Basophil was not observed in any of the patient included in study. Monocyte was found significant in Vataj kasa as compare to Kaphaj and Pittaj kasa. Lymphocyte count was nearly equal for all three Kasas. i.e., there was no significant difference between lymphocyte count of three Kasa – Vataj, Pittaj and Kaphaj.